Gold‐Loaded Nanoporous Iron Oxide Cubes Derived from Prussian Blue as Carbon Monoxide Oxidation Catalyst at Room Temperature. Issue 47 (18th December 2018) - Tanaka, Shunsuke; Zakaria, Mohamed Barakat; Kaneti, Yusuf Valentino; Jikihara, Yohei; Nakayama, Tsuruo; Zaman, Mukter; Bando, Yoshio; Hossain, Md. Shahriar A.; Golberg, Dmitri; Yamauchi, Yusuke
Abstract: This work reports the preparation of carbon monoxide (CO) oxidation catalysts based on gold nanoparticles supported on nanoporous iron oxide cubes. By heat‐treating Prussian blue (PB) cubes at various temperatures between 250–450 °C in air, nanoporous iron oxide cubes with surface areas up to 100 m 2  g −1 are obtained. Owing to the relatively large surface area and nanoporous structure, the as‐synthesized iron oxide cubes can be loaded with up to 11 wt% of Au nanoparticles without significant aggregation. When employed for CO oxidation, the Au‐loaded nanoporous iron oxide cubes exhibit a high CO conversion rate of over 95% at room temperature under 0.1 L⋅min −1 of CO gas flow, with specific activity of up to 1.79 molCO ⋅gAu −1 ⋅h −1 . The high catalytic performance of the Au‐loaded nanoporous iron oxide cubes for CO oxidation is contributed by various factors, including: (i) the high surface area of the iron oxide cubes which leads to the availability of more sites for the adsorption of oxygen molecules to react with carbon monoxide to generate more carbon dioxide (CO2 ); (ii) the presence of nanopores which enhances the diffusivity of the reactant molecules during the catalytic reaction and improves dispersion of the deposited gold nanoparticles while also preventing their aggregation at the same time and (iii) the small size of the deposited gold nanoparticles (2‐5 nm) which falls within the ideal size of gold nanoparticles for achieving high CO conversion. Abstract : Here, we have utilized Prussian blue (PB) cubes as sacrificial templates for the preparation of nanoporous iron oxide cubes. Owing to their nanoporous architecture and large surface area, the PB derived iron oxide cubes is successfully loaded with a high amount of Au NPs up to 11 wt% without significant aggregation. The obtained hybrid material shows a high CO conversion of over 95% at room temperature.